A function f(x) has x intercepts of -3 and -5. What is the constant term in the function? F(x)=x^2+8x+

Answers

Answer 1
Answer:

Answer:

The constant term in the function is 5

Step-by-step explanation:

we have

f(x)=x^(2)+8x+b

where

b is the y-intercept or the constant term of the function

Remember that

The x-intercept is the value of x when the value of the function is equal to zero

so

For x=-3 ----> f(x)=0

For x=-5 ----> f(x)=0

substitute any of the intercepts in the function

For x=-3

0=(-3)^(2)+8(-3)+b

0=9-24+b

0=-15+b

b=15

f(x)=x^(2)+8x+15

Verify with the other intercept

For x=-5

0=(-5)^(2)+8(-5)+15

0=25-40+15

0=0 ---> is true

therefore

The constant term in the function is 5


Related Questions

How do you describe a way to check the correctness of a division answer that has no remainder
What’s the product of 0.54(8)
Which of the following expressions is equal to tan245°?
Johnson high school has total enrollment of 1829 students. Sean tickets are sold for the basketball season and 604 students but the tickets. About what percent body purchased Season tickets
Please and thank you for helping !

A test has 100 questions. Cora got 85 questions correct. What decimal shows the part of the test she answered correctly? What decimal shows the part of the test she answered incorrectly?model the decimals below.

Answers

Cora got 85% of it correct so the decimal form would be 0.85
85/100 would be what she got CORRECT, and then 15/100 would be what she got INCORRECT. You can easily make them both decimals, because it is over 100, into .85 (the amount she got correct) and .15 (the amount she got incorrect).

FIRST ONE TO ANSWER GETS THE BRAINLIEST AND 20 POINTS!!! :)Parvinder wants to save $500 for a trip. Which inequality shows the least amount she must save each month for 6 months to accomplish this? Write an inequality and explian how got the answer.

Answers

Answer:

6x > and a line uder it the sign 500

Step-by-step explanation:

this menas pravader can save this money for six months any moth she wnats.

Answer:

6x> than the sign under the 500

Step-by-step explanation:

the coordinates for the vertices of a polygon are (1,4) , (6.4) , (6,1). what type of polygon is formed by thease points?

Answers

Because there are only three points that are given, one could say that it is a triangle, but to be more specific, it is a right triangle.

Hope this helps!

There is 3 points, so it is a triangle. 

Hope this helped, and please mark brainliest! :)

-7(3x)+2(3x-2) How do you simplify this and what is the answer.Im stumped

Answers

Answer:

-21x + 6x - 4

Step-by-step explanation:

First, distributive property.

-7(3x) = -21x

2(3x-2) = 6x - 4

Secondly, put those together.

-21x + 6x - 4

And that is your answer because you don't need to find the sum or x.

Consider the following system of equations: y = 5x + 6 y = −x − 7 Which description best describes the solution to the system of equations? Line y = 5x + 6 intersects line y = −x − 7.
Lines y = 5x + 6 and y = −x − 7 intersect the x-axis.
Lines y = 5x + 6 and y = −x − 7 intersect the y-axis.
Line y = 5x + 6 intersects the origin.

Answers

 y = 5x + 6
y = −x − 7 

5x + 6 = -x - 7
6x + 6 = -7
6x = -13
x = -13/6

y = 5(-13/6) + 6
y = -29/6

The solution is (-13/6, -29/6) and that tells us that the two ines do not intersect at the origin or any of the two axis. If they intersected at the origin, then the solution should have been (0, 0). If they intersected at the x-axis, the solution should have been (x, 0). If the two lines intersected at the y-axis, the solution would have been (0, y).

The answer is A) 
Line y = 5x + 6 intersects line y = −x − 7.

Answer:

The answer is A. Line y = 5x + 6 intersects line y = −x − 7.

Hope This Helps!

Y-x=02x-5y=9

Y-5=2x
Y-3x=-1

Anyone good at substitution that could do these two problems for me?

Answers

1.) y-x=0 and 2x-5y=9
 
Lets take the first equation (since it is the easiest to use for the substitution process) and set y equal to x by adding x to both sides.

y=x

Then we will substitute this into the second equation like this...

2x-5(x)=9

2x-5x=9

Combine like terms...

-3x=9

Divide both sides by -3...

x=-3 

^^^ That's the answer!


2.) y-5=2x and y-3x=-1

Again let's use the first equation and set I equal to y by adding 5 to both sides...

y=2x+5

Now let's substitute this into the second equation...

(2x+5)-3x=-1

2x+5-3x=-1

Now lets put the terms in order and then combine like terms...

-3x+2x+5=-1

-1x+5=-1

Now, let's subtract 5 to both sides...

-1x=4

Then divide both sides by -1...

x=4

^^^ That's the answer for #2!


Hope that helped! :-)